-3.6u+1.8=-1.8

Simple and best practice solution for -3.6u+1.8=-1.8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3.6u+1.8=-1.8 equation:


Simplifying
-3.6u + 1.8 = -1.8

Reorder the terms:
1.8 + -3.6u = -1.8

Solving
1.8 + -3.6u = -1.8

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-1.8' to each side of the equation.
1.8 + -1.8 + -3.6u = -1.8 + -1.8

Combine like terms: 1.8 + -1.8 = 0.0
0.0 + -3.6u = -1.8 + -1.8
-3.6u = -1.8 + -1.8

Combine like terms: -1.8 + -1.8 = -3.6
-3.6u = -3.6

Divide each side by '-3.6'.
u = 1

Simplifying
u = 1

See similar equations:

| -0.7-5.6=-3.5 | | 25*100=5*(500-x) | | 27a^2+39ad+14d^2= | | 12d^2-13ds-35s^2= | | 20b^3-41b^2+20b= | | 5a-2=a+18 | | 7x+38=248 | | dx+b=2(x-d) | | 44b^2-208b-60= | | 9m+3m= | | 9k=3 | | 32r^5-60r^4-27r^3= | | 3x^3+x^2-8x+4=0 | | 7000d=63.5 | | 0.4v+2.4=-5.4v-3.4 | | 0.4a+2.4=-5.4v-3.4 | | 32s^5-76s^4-33s^3= | | -3+(5z+9)=(7z+5)-6 | | 12x^2-8xy-20y^2= | | -0.8z+3.3=0.9 | | -6-6+20x=5(4x-5)+13 | | -0.8a+3.3=9.9 | | -3x-10=-4 | | 3a=9a+24 | | 6g^2+13gc+6c^2= | | -2t-1=3t-16 | | 3z-13=-10 | | 4x-2y=-12 | | -2+6=4v-6v | | 42m^2-29mn-5n^2= | | 9x+-2=4x+9 | | 0=8x+39 |

Equations solver categories